Singapore : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
Singapore's economy is slowing against the backdrop of a deteriorating external environment and a softening of exports. The main near-term risks are a protracted slowdown in advanced economies and a sharp increase in global financial stress. Given Singapore's openness, these shocks would hit the economy severely through weaker exports, reduced capital inflows, slower credit, and a fall in financial market activity. The authorities have sufficient policy space to deploy a decisive response in case these risks materialize. A rapid increase in foreign currency lending may also raise the risk of funding strains.